The TERE1 protein interacts with mitochondrial TBL2: Regulation of trans‐membrane potential, ROS/RNS and SXR target genes. Issue 9 (18th July 2013) - Fredericks, William J.; McGarvey, Terry; Wang, Huiyi; Zheng, Yongmu; Fredericks, Nathaniel J.; Yin, Hankun; Wang, Li‐Ping; Hsiao, Wayland; Lee, Rob; Weiss, Jayne S.; Nickerson, Michael L.; Kruth, Howard S.; et al.
Abstract We originally discovered TERE1 as a potential tumor suppressor protein based upon reduced expression in bladder and prostate cancer specimens and growth inhibition of tumor cell lines/xenografts upon ectopic expression. Analysis of TERE1 (aka UBIAD1) has shown it is a prenyltransferase enzyme in the natural bio‐synthetic pathways for both vitamin K‐2 and COQ10 production and exhibits multiple subcellular localizations including mitochondria, endoplasmic reticulum, and golgi. Vitamin K‐2 is involved in mitochondrial electron transport, SXR nuclear hormone receptor signaling and redox cycling: together these functions may form the basis for tumor suppressor function. To gain further insight into mechanisms of growth suppression and enzymatic regulation of TERE1 we isolated TERE1 associated proteins and identified the WD40 repeat, mitochondrial protein TBL2. We examined whether disease specific mutations in TERE1 affected interactions with TBL2 and the role of each protein in altering mitochondrial function, ROS/RNS production and SXR target gene regulation. Biochemical binding assays demonstrated a direct, high affinity interaction between TERE1 and TBL2 proteins; TERE1 was localized to both mitochondrial and non‐mitochondrial membranes whereas TBL2 was predominantly mitochondrial; multiple independent single amino acid substitutions in TERE1 which cause a human hereditary corneal disease reduced binding to TBL2 strongly suggesting the relevance of this interaction. Ectopic TERE1 expression elevated mitochondrial trans‐membrane potential, oxidative stress, NO production, and activated SXR targets. A TERE1‐TBL2 complex likely functions in oxidative/nitrosative stress, lipid metabolism, and SXR signaling pathways in its role as a tumor suppressor. J. Cell. Biochem. 114: 2170–2187, 2013. © 2013 Wiley Periodicals, Inc.